Synthesis and morphological characterization of nanoporous aluminum oxide films by using a single anodization step - Bruera, Florencia Alejandra (2019)
Nanoporous anodic aluminum oxide (AAO) films play an important role in nanotechnology due to their easily adjustable morphological properties and wide range of applications. Thus, a deep and systematic characterization of the morphological properties of these coatings is essential. The most important variables in the synthesis of nanoporous AAO films include the anodization voltage, nature, concentration and temperature of the electrolyte, which, combined, result in pores of different sizes and geometries. In the present work, AA 1050 alloy was used to synthesize AAO films, using 0.3 and 0.9 M oxalic acid as the electrolyte and combining different electrolyte temperatures (20, 30 and 40 °C) and anodizing voltages (30, 40 and 60 V), with the aim to correlate the morphological properties of the coatings with the synthesis parameters of a single anodization step. The coatings obtained were characterized by optical microscopy and scanning electron microscopy, determining pore diameter, interpore distance, pore density and coating thickness. The results showed that, by varying the anodic synthesis conditions, it is possible to obtain coatings with a pore diameter between 21 and 97 nm, an interpore distance between 59 and 138 nm, pore density between 2.8 × 10 10 and 5.4 × 10 9 pores/cm 2 and thicknesses between 15 and 145 μm. In this way, the right combination of synthesis variables allows synthesizing AAO coatings with morphological characteristics best suited to each particular application.